Ranking Asia-Pacific cities: Economic performance of multinational corporations and the regional urban hierarchy. - Csomós, György; Derudder, Ben (Bulletin of Geography. Socio-economic Series, 2014)
Over the past decade the world economy has undergone significant changes with an impact not only on national economies but also on the key cities from which that world economy is largely being controlled. In this study, we use Forbes' 'Global 2000' data on the headquarter location and size of the world's leading multinational corporations in order to examine the shifting relative position of leading Asia-Pacific cities as command and control centres in this increasingly important part of the world economy. Comparing cities' positions in 2006 and 2011, we present that Tokyo, which assumed a leading role in the region for decades, has seen a major decline in its command and control function, while Beijing now represents almost as much as command and control as the Japanese capital. Beijing's fast growth in command and control is also found for Chinese cities, albeit that Beijing clearly dominates the other Chinese cities. In addition, we present that shifting patterns of command and control also hinge on the sectors dominating the Forbes 2000 ranking.